A multi-center trial-based economic evaluation of the SELF-program: A function-focused care program for nursing staff providing long-term care for geriatric clients in nursing homes compared to care as usual - Ruben M.W.A. Drost; Ghislaine A.P.G. van Mastrigt; Stan Vluggen; Silke F. Metzelthin; Michel H.C. Bleijlevens; Getty Huisman-de Waal; Janneke M. de Man-van Ginkel; Sandra M.G. Zwakhalen (PLoS ONE, 2025)
Introduction This study aims to evaluate the cost-effectiveness and cost-utility of the SElf-reliance, autonomy, Life quality, and Functionality-program (SELF) for nursing staff in nursing homes who provide long-term care to geriatric clients as compared to care as usual from a societal perspective. Methods The economic evaluation ran parallel to a two-arm multicenter cluster-randomized trial, in which the nursing staff in the intervention group received the SELF-program, and nursing staff in the control group received no program and delivered care as usual. Outcomes and societal costs for clients who received care from nursing staff were measured using questionnaires at baseline, 3 months, and 6 months. The main measures included Activities of Daily Living, as measured with the GARS-4, utility scores as measured with the EQ-5D-5L, and costs related to the intervention, informal care and health service utilization. Cost-effectiveness and cost-utility analyses were conducted, calculating incremental cost-effectiveness ratios from societal and healthcare perspectives. Bootstrap analyses were performed, with results displayed on cost-effectiveness planes and acceptability curves. Results In total, 28 wards with a total of 241 clients were randomized (intervention, n = 115; control group, n = 126) From a societal perspective, care delivered in the intervention group led to lower costs than care as usual over the 6-month period, with incremental costs of -€584. In terms of the GARS-4 sum score, the SELF-program resulted in a favorable decrease of 0.81 points, and in terms of QALYs, it resulted in a favorable increase of 0.07. From a healthcare perspective, the incremental costs amounted to €556, with ratios of €410 per point reduction on the GARS-4 and €8,356 per QALY. Conclusions The main analysis suggests that over 6 months from a societal perspective for both outcomes, the intervention is cost-effective as compared to care as usual. Trial registration International Clinical Trials Registry Platform: NL9189; https://trialsearch.who.int/Trial2.aspx?TrialID=NL9189